Associations Between Dietary Inflammatory Index and Sex Hormones Among 6- to 19-Year-Old Children and Adolescents in NHANES 2015–2016 - Ma, Yuxia; Li, Ruiqiang; Zhan, Wenqiang; Huang, Xin; Zhou, Yutian; Sun, Yan; Tian, Hao; Zhu, Huichen; Yin, Bowen (Frontiers in Endocrinology, 2022)
Objectives This study aimed to assess the relationship between dietary inflammatory index (DII) and sex steroids in children (6-11 years old) and adolescents (12-19 years old) in the U.S. National Health and Nutrition Examination Survey, 2015–2016. Methods Participants between the ages of 6-19 have 24-hour dietary intake data, serum sex hormones [total testosterone (TT), estradiol (E2)], and sex hormone-binding globulin (SHBG) available data (n = 1382). The free androgen index (FAI) is calculated as TT divided by SHBG and the ratio of TT to E2 (TT/E2). The constructed puberty state is defined as high levels of steroid hormones (TT≥50 ng/dL in men, E2≥20 pg/ml in women) or onset of menarche. Multiple linear regression analysis was stratified by gender-age and gender-pubertal status groups to evaluate the association between DII and sex hormone levels. Results After adjusting for covariates, the association between consecutive DII and sex hormone indicators by gender and age group. In male adolescents, DII was always negatively associated with TT (P-trend = 0.09), FAI (P-trend = 0.03) and E2 (P-trend = 0.01), and monotonically positively associated with SHBG (P-trend = 0.02).In female adolescents, with the increase of DII, a significant positive correlation with SHBG was observed (β 0.017, 95%CI: 0.009,0.053) (Table 3). Among female adolescents, a significant negative association between DII and TT and a significant positive association between SHBG were observed in this group. Moreover, DII was positively associated with SHBG of prepubertal males and negatively associated with FAI of prepubertal females. Conclusions DII was associated with decreased levels of certain sex steroid hormones (TT, FAI, and E2) and increased levels of SHBG in adolescents or pubertal individuals, with the associations presenting somewhat sex-dependent pattern. However, there is little evidence that there is a significant association in children or prepubertal children. Further research needs to be carried out to verify our results.